Stability of supersonic boundary layer on permeable surface - Gaponov, S.A.; Ermolaev, Yu.G.; Kosinov, A.D.; Lysenko, V.I.; Semionov, N.V.; Smorodsky, B.V. (Archives of Mechanics, 2014)
In the present study we have performed combined theoretical and experimental investigation of the surface permeability influence on the linear stability of the supersonic flat-plate boundary layer at free-stream Mach number M = 2. Good quantitative agreement was obtained between the data calculated by the linear theory of stability and the data obtained in experiments with artificially generated disturbances performed on models with various porous inserts.